An Uneasy Relationship Norfolk Island and the Commonwealth of Australia - O'Collins, Maev (ANU Press, 2010)
The situation of Norfolk Island, as a territory of the Commonwealth of Australia, is one of the historical anomalies in governance, which has persisted since 1914. It reflects the direct historical linkages between the British Crown and those Norfolk Islanders who were descendants of Pitcairn Islanders of Mutiny on the Bounty fame. Yet, once Federation was in the wind, the British Government, against the expressed wishes of the Norfolk Island community, sought to divest itself of all responsibility for Norfolk Island. There is a curiously 'Yes Minister' quality about the negotiations which lead to the final take-over by Australia, and the appointment of the first Commonwealth Administrator of Norfolk Island. The direct involvement of Atlee Hunt, then Secretary of the Department of External Affairs, eventually ensured the appointment of Michael Vincent Murphy. In order to achieve this end, Hunt had to fend off other applicants who were busy ingratiating themselves with the Minister for External Affairs Patrick McMahon Glynn and the then Prime Minister Joseph Cook. This is essentially a study of the relationships between governors, politicians, public servants and community leaders during the years which followed the take-over of Norfolk Island, and of the struggle of one Norfolk Islander, Charles Chase Ray Nobbs, against Australian administrative authority